Optimizing Information Media Management in the Digital Era for National Resilience - Gatot Repli Handoko; Swastiningsih; Heru Yulianto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of digital media has transformed information dissemination in Indonesia, but it also fuels the spread of hoaxes, hate speech, and divisive content, threatening national resilience. This study aims to analyze how information media management can be optimized to strengthen national unity and security. Using a qualitative descriptive-analytical approach, the research examines government reports, academic studies, and news articles to explore challenges and strategies in managing digital media. The findings reveal that hoaxes and hate speech, particularly on social media, erode public trust and deepen social polarization, with significant cases during the coronavirus disease pandemic. Government efforts, including cyber patrols and public education, are hindered by weak coordination among institutions and low media literacy among citizens. Digital infrastructure, such as media centers and online reporting platforms, shows potential but faces limitations due to budget constraints and lack of expertise. Strengthening media management requires improved institutional coordination, enhanced digital tools, and widespread media literacy programs. This study concludes that a comprehensive approach combining technology, regulation, and public engagement is essential to counter disinformation and foster a resilient society capable of maintaining national values and unity in the digital era.